(untitled) (Indonesian Tourism Justice Review, 2025)
Cultural appropriation remains a contentious issue in the tourism industry, particularly in contexts where indigenous cultures are commodified for the consumption of tourists. This paper explores the ethical implications of cultural representation in Indonesia’s tourism industry, focusing on the portrayal of indigenous traditions, art, and rituals. The study investigates how tourism marketing, performances, and commercialized cultural practices may misrepresent or exploit indigenous cultures, raising concerns about cultural appropriation and justice. Through interviews with indigenous leaders, cultural activists, and tourism operators, the paper examines the dynamics of cultural exchange and the power relations that shape cultural representation in tourism. The research highlights the risks of cultural erosion and the need for ethical guidelines to ensure that indigenous cultures are represented with authenticity and respect. The paper advocates for a tourism model that emphasizes cultural preservation, community consent, and the empowerment of indigenous people in shaping their cultural narratives. In conclusion, the study proposes a set of best practices for ethical tourism that can help mitigate the negative effects of cultural commodification.